Dinamika Perubahan Suhu dan Klorofi-a Terhadap Distribusi Ikan Teri (Stelophorus sp) di Perairan Pantai Spermonde, Pangkep - Safruddin Safruddin; Mukti Zainuddin; Joeharnani Tresnati (Jurnal IPTEKS Pemanfaatan Sumberdaya Perikanan, 2014)
The distribution of anchovies (Stelophorus spp) in the Spermonde coastal waters, Pangkep, was studied from satellite remotely sensed environment and catch data, using Geographic Information Systems (GIS) and Generalized Additive Model (GAM). The goal of this preliminary study was to investigate the relationship between sea surface temperature (SST) and sea surface chlorophyll-a concentration (SSC), and anchovies distribution. To describe their relationship, SST and SSC derived from Aqua/MODIS satellite were overlain with the positions of experimental fishing by local fishermen’s lift net (“Bagan perahu”). The experimental lift net operations were conducted in April to May 2008. The findings of this study showed that most of the anchovies distribution occurred in the coastal area. Anchovies distribution tended to be highest in the specific temperature of 28.8 - 29.3C and chlorophyll-a of 1.5 ‒2.5 mg.m . Furthermore, the SST and SSC in the coastal waters of Spermonde play a great role in determining the variability of the anchovies quantitative distribution in the study area. The results were supported by GAM prediction.  Due to lack of robust data, there is no detailed information on the optimum habitat preference of anchovies. Future work is needed to reveal the preferred habitat of anchovies with the consideration of more oceanographic parameters.